If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 180 + -1(12x + -36) + -1(16x + -24) + -88 = 0 Reorder the terms: 180 + -1(-36 + 12x) + -1(16x + -24) + -88 = 0 180 + (-36 * -1 + 12x * -1) + -1(16x + -24) + -88 = 0 180 + (36 + -12x) + -1(16x + -24) + -88 = 0 Reorder the terms: 180 + 36 + -12x + -1(-24 + 16x) + -88 = 0 180 + 36 + -12x + (-24 * -1 + 16x * -1) + -88 = 0 180 + 36 + -12x + (24 + -16x) + -88 = 0 Reorder the terms: 180 + 36 + 24 + -88 + -12x + -16x = 0 Combine like terms: 180 + 36 = 216 216 + 24 + -88 + -12x + -16x = 0 Combine like terms: 216 + 24 = 240 240 + -88 + -12x + -16x = 0 Combine like terms: 240 + -88 = 152 152 + -12x + -16x = 0 Combine like terms: -12x + -16x = -28x 152 + -28x = 0 Solving 152 + -28x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-152' to each side of the equation. 152 + -152 + -28x = 0 + -152 Combine like terms: 152 + -152 = 0 0 + -28x = 0 + -152 -28x = 0 + -152 Combine like terms: 0 + -152 = -152 -28x = -152 Divide each side by '-28'. x = 5.428571429 Simplifying x = 5.428571429
| 2+4x=-78 | | x(3x-4)=180 | | X+(X*.1)=40.85 | | 3x+84=15 | | 3/8n=5/6 | | 2(7s+3)-8s=2(3s+4)-12 | | 3x+13+25=2+7x | | 56-6=8 | | 3x-2/2x+1=-2 | | -9(2w-9)=0 | | K^2+5k+8=2 | | 50y=200 | | 18x-4x=9-3x | | 4(4-a)-2(a-4)=-10a-2a | | 4x-(30-x)+25=80 | | 15+4x+60=11x+12 | | 30+you=7 | | 2*(24/2y)*y=48 | | 5u(8u-1)=0 | | 4y=14-2x | | -1=-4+b | | (x^69-i^69)(x^69+i^69)=0 | | dy/dx=1/(2x-y^2) | | 7(x+2)=2x+57 | | 108=4z | | y=1/(2x-y^2) | | 0.5=1-e^-((t-1)/10) | | 4(4-a)-2(a-4)=-10-2a | | -2(5v-3)+3v=3(v+4) | | 7x+19+2x+15=133 | | -4h+6=-6h-8 | | 21b=14+b |